A novel technique for endobronchial blocker placement for one‐lung ventilation in children under 2 years. Issue 6 (7th March 2018) - Guo, X.; Song, X.; Chen, X.; Liu, W.; Wang, H.; Xia, H.
Abstract : Background: The present study aimed to report our clinical experience with intraluminal calculated distance for endobronchial blocker placement (ICEB) and to find out whether ICEB could reduce the number of hypoxemia episodes during blocker placement compared with extraluminal blocker placement for one‐lung ventilation in children under the age of 2 years. Methods: The medical records of all children under the age of 2 years with a 5 French (F) or 4F WeiLi (WeiLi medical Inc, Guangzhou, China) endobronchial blocker for one‐lung ventilation in thoracic surgery from July 2015 through July 2016 were retrospectively reviewed. After November 2015, one‐lung ventilation was achieved using the ICEB technique, while before November 2015, extraluminal blocker placement was used. The success rate of blocker placement, quality of lung deflation, number of hypoxemia episodes, blocker dislodgement, and successful reposition after dislodgement were compared between the two groups. Result: The incidence of hypoxemia episodes during blocker placement was lower in the ICEB group compared to the extraluminal placement group. Moreover, the success rate of blocker reposition during the operation was higher in the ICEB group than the extraluminal placement group. The success rate of endobronchial blocker placement was similar between the two groups. Conclusions: Intraluminal calculated distance for endobronchial blocker placement is a feasible method to achieve lung isolation and could reduce hypoxemia episodes during blocker placement in children under the age of 2 years.